2019
DOI: 10.1002/adma.201807540
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Solar Absorption of Atomically Thin 2D Carbon Nitride Sheets for Enhanced Visible‐Light Photocatalysis

Abstract: Atomically thin 2D carbon nitride sheets (CNS) are promising materials for photocatalytic applications due to their large surface area and very short charge‐carrier diffusion distance from the bulk to the surface. However, compared to their bulk counterpart, CNS' applications always suffer from an enlarged bandgap and thus narrowed solar absorption range. Here, an approach to significantly increase solar absorption of the atomically thin CNS via fluorination followed by thermal defluorination is reported. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
147
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(155 citation statements)
references
References 41 publications
8
147
0
Order By: Relevance
“…[ 41 ] As for photocatalysis, an ultrathin structure is also capable of rapid transporting photo‐excited electrons and giving sufficient active sites for HER. [ 42–44 ] Considering the above merits of bi‐metal phosphide and an ultrathin 2D structure, thus, it motivates us to design an ultrathin 2D NiCoP nanosheets to achieve efficient and stable electrocatalytic and photocatalytic water splitting performances, yet it is still to report.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] As for photocatalysis, an ultrathin structure is also capable of rapid transporting photo‐excited electrons and giving sufficient active sites for HER. [ 42–44 ] Considering the above merits of bi‐metal phosphide and an ultrathin 2D structure, thus, it motivates us to design an ultrathin 2D NiCoP nanosheets to achieve efficient and stable electrocatalytic and photocatalytic water splitting performances, yet it is still to report.…”
Section: Introductionmentioning
confidence: 99%
“…These shortcomings severely limit its development in the field of photocatalysis. To address these issues, various studies have focused on the synthesis of ultrathin 2D nanosheets by using fluorination followed by thermal defluorination, liquid phase exfoliation, alkaline activation with thermal exfoliation, self‐modification through successive thermal treatment, Zn‐assisted thermal treatment, and salt‐mediated synthesis . The apparent advantages of such kinds of 2D nanosheets include short diffusion length from the bulk to the interface to reduce the transfer resistance, low recombination probability of photogenerated carriers, and enlarged specific surface areas providing abundant reactive sites .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have confirmed that exfoliating bulk g‐C 3 N 4 with ultrathin thickness is an effective method to overcome above problems. [ 78–87 ] Meanwhile, g‐C 3 N 4 is an analogous of graphene, in which the interaction between different layers is van der Waals forces. Therefore, it is convenient to synthesize g‐C 3 N 4 with ultrathin thickness.…”
Section: Metal Free Thin‐layered Photocatalystmentioning
confidence: 99%
“…[ 133 ] Aside from OVs, other kind of anion vacancies (C, I, N, and S vacancies) have also been reported. [ 86,110,134,135 ]…”
Section: Strategies For Improving Thin‐layered Materials Photocatalytmentioning
confidence: 99%